Comparison of GEOS‐Chem aerosol optical depth with AERONET and MISR data over the contiguous United States. Issue 19 (10th October 2013) - Li, Shenshen; Garay, Michael J.; Chen, Liangfu; Rees, Erika; Liu, Yang
<x xml:space="preserve">Abstract</x> [1] Aerosol optical properties simulated by the global 3‐D tropospheric chemistry and transport model Goddard Earth Observing System (GEOS)‐Chem (GC) from 2008 to 2010 over the contiguous United States were evaluated with ground observations from Aerosol Robotic Network (AERONET) sites and aerosol products reported by the Multiangle Imaging Spectroradiometer (MISR). Overall, the correlation coefficient (r) and regression slope between AERONET and GC2° × 2.5° (2° latitude × 2.5° longitude) daily total column aerosol optical depth (AOD) were 0.6 and 0.51, respectively. After using the nested GC0.5° × 0.667° model to control for spatial variability, removing several outliers, and averaging over a monthly timescale, the agreement was significantly improved to an r of 0.84 and a slope of 0.75. Seasonal, hourly, and geographical statistics for GC0.5° × 0.667° and AERONET AODs show a similar data range and variation, with higher mean values in the summer, the evening, and in the eastern U.S. Smaller correlation coefficients are seen in the summer and winter, in the evening, and in the western U.S. To investigate the optical properties of major GC tracers, MISR level 2 aerosol products were used to calculate inorganic aerosol, dust, and absorbing non‐dust AOD. Both GC and MISR suggest that on average, inorganic aerosol has the highest AOD (GC: 0.071, MISR: 0.089) nationally, followed by absorbing non‐dust species (GC: 0.025, MISR: 0.041), and dust (GC: 0.013, MISR: 0.014). The large discrepancies in our intercomparison are due to GC underestimation of inorganic aerosol levels during all four seasons in the western U.S. and dust during summer in the eastern U.S., along with overestimation of summertime‐absorbing non‐dust species over the northwestern U.S. These uncertainties are attributed to underestimation of inorganic aerosol emissions in more polluted western regions, the transport of Sahara dust in the summer, misuse of the fire files, MISR retrieval uncertainties in the surface, and choice of aerosol models.